FACTORS AFFECTING MATERNAL COMPLIANCE IN THIRD TRIMESTER ANTENATAL CARE AT NURUSSALAM HEALTH CENTER IN EAST ACEH DISTRICT IN 2024 - Risna Fazlaini; Frisca Fazira; Ummu Aiman; Muliana (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The high maternal mortality rate in Indonesia is related to many factors, one of which is pregnancy, where complications during pregnancy are not detected because pregnant women do not utilize ANC. Problems that occur in pregnancy can be prevented by pregnancy check-ups. The importance of ANC visits is not yet a top priority for most pregnant women. Based on Green's theory, there are predisposing factors (education, knowledge), reinforcing factors (husband support) and enabling factors that can influence a person's behavior. This study aims to determine the factors that influence the compliance of pregnant women in third trimester pregnancy checks at the Nurussalam Health Center, East Aceh Regency in 2024. This type of research is observational analytic, survey method and cross sectional design. This study was conducted at the Nurussalam Health Center, East Aceh Regency in April-May 2024. The sample was TMT III pregnant women totaling 40 people taken by accidental sampling. The study showed that the compliance of TMT III pregnancy examination in the majority was not compliant, namely 24 respondents (60%). There is a relationship between maternal education and compliance with TMT III pregnancy check-ups with a Pvalue = 0.001 < a = 0.05. There is a relationship between maternal knowledge with TMT III pregnancy check-up compliance with a Pvalue = 0.014 < a = 0.05. There is a relationship between husband's support with TMT III pregnancy check-up compliance with a Pvalue = 0.021 < a = 0.05. It is hoped that this study can be a reference to be able to check their pregnancy regularly in accordance with current regulations, so that obstetric and neonatal emergencies can be managed early so as to reduce morbidity and mortality of both mothers and babies.